TEXT MESSAGING AS A PREDICTOR OF ORTHOGRAPHIC PROCESSING OF BS-CRIMINOLOGY STUDENTS AT UNIVERSITY OF MINDANAO TAGUM COLLEGE: BASIS FOR AN INTERVENTION PROGRAM - Genesis G. Genelza (Galaxy International Interdisciplinary Research Journal, 2022)
There is a plethora of reasons for why exposure to misspelled words has a great stimulus on learners’ capacity to integrate orthographic information, predominantly in this time where electronic communication is growing. Mobile phones, online gaming, text messaging, and social media are just a few of the communication technology advancements that are opening up new channels for social engagement and contact. The descriptive correlation study is aimed to determine the significant relationship between text messaging and orthographic processing of BS-Criminology Students at University of Mindanao Tagum College. The results revealed that there is a great correlation between the two variables with a p-value of 0.0051. The evidence supporting the claim that text messaging has a negative influence on language abilities and orthographic processing has been transparent and observable at some point or occasion. With this, teachers and students take on particular identities and roles in their interactions with one another, which aids in the development of their conceptions of what learning is as a process and as a body of knowledge through implementing the suggested speaking improvement exercises created by the researcher, and so the students will be equipped to use the language appropriately at any occasions.